Statins – hope for effective treatment of endometriosis? - Szyłło, Krzysztof; Górski, Jarosław; Kulig, Bartosz (Menopause Review/Przegląd Menopauzalny, 2007)
Endometriosis is defined as the presence of endometrial tissue (glandular epithelium and stroma) outside the uterine cavity. It occurs in 10-15% of women in reproductive age, but in the group of women treated for infertility this frequency grows to 50-60%. The main symptoms are: chronic pelvic minor pains not related to menstruation, painful menstruations, dyspareunia. The disease considerably worsens both physical and mental quality of life. Its complex and not fully recognized aetiology also results in therapeutic difficulties. This article presents an overview of available literature describing attempts of statin administration in treatment of endometriosis. Hope connected with statin usage is particularly important since none of the previously applied substances met the expectations. Statins effectively inhibit proliferation of stromal cells and angiogenesis in a dose-dependent manner. The outcomes of the research, depending on the dose of the drug and the way of application (per os or by subcutaneous injection) generate new opportunities of endometriosis treatment. Statins seem to have hardly any side effects. In addition, they do not affect fertility, which is important during pregnancy planning by women who suffer from infertility. The results of the medical research conducted so far are not numerous, but are promising, creating new therapeutic perspectives. However, they still need to be verified during examination on people.